VD_FINDINFO Jug / 2016 / 384 vom 27. Januar 2016 - VD Tribunal cantonal (2016)
LÉSION CORPORELLE GRAVE, NÉGLIGENCE, REJET DE LA DEMANDE, DÉPENS, APPRÉCIATION DES PREUVES | 106 CP, 12 al. 3 CP, 125 CP, 34 CP, 42 al. 1 CP, 42 al. 4 CP, 31 al. 1 LCR, 34 al. 1 LCR, 34 al. 3 LCR, 10 CPP (CH), 433 al. 1 CPP(CH)